(untitled) (International Journal of Banking and Finance, 2012)
This paper identifies the association between off balance sheet businesses and a number of determinants identified for the banking sectors of the Gulf Cooperation Council countries. The Fixed Effects Least Squares Dummy Variable Model is used to identify the determinants for a large sample of 64 banks over a recent fifteen-year period. The results reveal that bank-specific variables have important roles in influencing off balance businesses. As for the regulatory variable, capital items are less important, which is contrary to the long-held market discipline hypothesis, under which secure banks are predisposed to engage in more off balance businesses. The macroeconomic variable reveals that higher real GDP growth does not necessarily cause an increase in the off balance activities. However, its positive impact indicates that the off balance business actions follow business cycles, and the overall growth of economy. Prudential regulators, as a policy matter, need to consider region-wide implications of these findings. This is important given the fact that regulating how off balance business is conducted in the region would influence costs and the scope of banks, hence also the monetary policy.